Subalternitas dan Representasi Ganda dalam Cerita Pendek "Kalabaka" Karya Iksaka Banu - Fadilah, Yuniardi (BEBASAN Jurnal Ilmiah Kebahasaan dan Kesastraan, 2020)
In the short story titled "Kalabaka" which revolves around the colonial period, the problem of the colonizers and the colonized always involves the problem of the East-West dichotomy. This short story also concerns about power relations, identity, and space. Related to the power relations between the colonizers and the colonized, then, the role of the dominant and subalterns emerged. In this case, the dominant one is certainly the colonialist, and subalterns are the colonized indigenous people. These issues make this research choose to use Gayatri Spivak's view of subalternity and representation. Therefore, the research seeks to explain the subaltern position constructed by the structure of the short story and the role of representation as a form of the perpetuation of colonialism. In the short story "Kalabaka", subalternity is created because of the dominant position of the colonialist leader over the indigenous people. This Western perspective then always looks down on the East. This then led to the emergence of representations that tried to fill the position of Kalabaka figures and the Banda community by Dutch figures in the story.